The Implementation of the Reading Comprehension Method in Arabic Language Learning at Islamic Senior High Schools: Teachers’ and Students’ Perspectives - Isop Syafei; Kania Herliana Kurnia; Faiza Alipvia Khoerunnisa (Gunung Djati Conference Series, 2026)
This study aims to examine the implementation of the reading comprehension method in improving Arabic language learning at Madrasah Aliyah from the perspectives of teachers and students. This research employs a descriptive qualitative approach to provide an in-depth description of how the reading comprehension method is applied in Arabic language learning at Madrasah Aliyah, based on insights from both teachers and students. Primary data were obtained through classroom observations, in-depth interviews, and documentation, while secondary data consisted of the curriculum, syllabus, lesson plans, teaching materials, and supporting literature. Data collection was carried out through observation, interviews, and documentation to obtain authentic and comprehensive information. Data were analyzed using an interactive model that includes data reduction, data display, and conclusion drawing, repeatedly conducted until valid findings were produced. The results indicate that both teachers and students perceive the reading comprehension method as highly important and effective in Arabic language learning. Teachers implement the stages of pre-reading, while-reading, and post-reading through strategies such as skimming, scanning, annotating, guided reading, and reciprocal teaching. Students reported that the method helps them learn more systematically, increases motivation, and enhances learning autonomy. Visual media also strengthens reading interest. Challenges encountered include heterogeneous student abilities, limited vocabulary, short instructional time, and the lack of varied reading texts. Despite these constraints, the method remains effective in improving text comprehension and critical thinking skills.